Dietetic value of vegetables - Forsyth, Hattie L. (My University, 1904)
Introduction: As civilization advances, and the composition, and cookery of vegetables are known, there is a larger amount of them used in our daily food. The potato, now so widely used, and forming a part of our daily diet, was entirely unknown in the eastern continent previous to the discovery of America. The same is true of many of the other common vegetables. The vegetables contain all the proximate food principles that are found in the animal foods. Potatoes are rich in carbohydrates, beans in nitrogenous matter, and nuts in fats. They are important foods on account of being the chief source of the starches and sugars, and also of being a much cheaper food than animal food. Though they are not as highly flavoured as many of the animal foods, they have an advantage…
Citation: Forsyth, Hattie L. Dietetic value of vegetables. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Vegetables; Diet; Nutrition; Food; Cooking; Theses; Manuscripts (documents)